Short‐Term Dynamics of Soil Physical Properties as Affected by Compaction and Tillage in a Silt Loam Soil. Issue 1 (11th October 2018) - Hu, Wei; Tabley, Frank; Beare, Mike; Tregurtha, Craig; Gillespie, Richard; Qiu, Weiwen; Gosden, Peg
Abstract : Core Ideas: Compaction deteriorated soil physical quality especially for the top 0.1‐m layer and tilled soils. Tillage temporarily improved soil physical quality in compacted soils. No‐till for establishing autumn forage crops can be used to mitigate the compaction effect. Short‐term variation in hydraulic properties may be significant for soil and crop modeling. This study investigated short‐term dynamics of soil physical properties as affected by tillage and compaction in a silt loam soil. After establishment of an autumn‐sown forage oat ( Avena sativa L.) crop with either NT or intensive tillage (IT), five degrees of livestock compaction (0–261 kPa) were applied in winter using a "cow treading implement." A barley ( Hordeum vulgare L.) crop was then sown following shallow cultivation of the soil in spring. After 2 yr of sheep‐grazed pasture, tillage significantly improved the soil physical quality in the 0‐ to 0.2‐m layer. Compaction significantly deteriorated soil physical quality, by, for example, decreasing macroporosity, available water content, and saturated hydraulic conductivity. Compared with IT and the top 0.1‐m soil layer, soil physical properties in NT and the subsurface 0.1‐ to 0.2‐m layer were more resistant to compaction. Irrespective of tillage, the topsoil (0–0.1 m) was more susceptible to physical degradation than the subsurface soil (0.1–0.2 m). Compaction and tillage effects on soil physical quality declined with time because of natural recovery and the shallow tillage used to establish the subsequent barley crop. This study demonstrated that using NT to establish an autumn‐sown forage crop can mitigate the adverse impacts of livestock treading on soil physical quality during subsequent grazing. Although tillage and compaction effects were short lived, soil physical properties were significantly different between every two adjacent measurement times. This highlights the need to consider the short‐term changes in soil hydraulic properties when modeling soil–crop systems.